Respuesta :
g(x)= 4-3(-3) would solve to be g(x)=13
g(x)= 4-3(0) would solve to be g(x)= 4
g(x)= 4-3(5) would solve to be g(x)= -19
Hope this helps
g(x)= 4-3(0) would solve to be g(x)= 4
g(x)= 4-3(5) would solve to be g(x)= -19
Hope this helps
The values of the given function when x = -3, 0, and 5 are 13, 4, and -11 respectively
From the question,
The given function is g(x) = 4 - 3x
We are to evaluate the function for the given values of x
- For when x = -3
put the value x = -3 into the function
That is,
g(x) = 4 - 3x becomes
g(-3) = 4 - 3(-3)
g(-3) = 4 + 9
g(-3) = 13
- For when x = 0,
Put the value x = 0 into the function
That is,
g(x) = 4 - 3x becomes
g(0) = 4 - 3(0)
g(0) = 4 - 0
g(0) = 4
- For when x = 5,
Put the value x = 5 into the function
That is,
g(x) = 4 - 3x becomes
g(5) = 4 - 3(5)
g(5) = 4 - 15
g(5) = -11
Hence, the values of the given function when x = -3, 0, and 5 are 13, 4, and -11 respectively
Learn more here: https://brainly.com/question/18684293